Thin empirics. (April 2019) - Simon, Dan
In the Target Article Relative Plausibility and Its Critics, Ron Allen and Michael Pardo set out to make the empirical claim that Relative Plausibility provides the best account of juridical proof. While I tend to agree with this conclusion, the article suffers from notable weaknesses. Allen and Pardo do not define a unit of analysis, they offer no testable hypotheses, and they present no data–all of which render the empirical claim befuddling. The empirical claim cannot be salvaged by the recruitment of the Story Model. For all its brilliance, the Story Model provides too narrow a foundation to sustain a general model of legal fact-finding. Allen and Pardo's reliance on holistic processing stands on sounder scientific grounds, but the casual referencing cannot amount to empirical proof. More importantly, Allen and Pardo refrain from reckoning with the implications of holism, and thus ignore both the promise and perils of the cognitive process they espouse. The experimental paradigm of Coherence Based Reasoning reveals a number of such implications. Notably, holism cannot deliver the objectivity and accuracy that Allen and Pardo seem to ascribe to it. Moreover, holistic processing entails a distortion of the evidence, which could lead to dismissing evidence that would otherwise raise a valid doubt, and inflate a hesitant fact-finder's confidence up to a firm conviction in the defendant's guilt. Holism also entails vast interconnectivity among the evidence items, which can trigger non-normative inferences and enable extra-evidential information to alter the fact-finder's perception of correctly-admitted evidence.